2019
DOI: 10.1016/j.crstbi.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of substrate-free E. coli Lon protease provides insights into the dynamics of Lon machinery

Abstract: Energy-dependent Lon proteases play a key role in cellular regulation by degrading short-lived regulatory proteins and misfolded proteins in the cell. The structure of the catalytically inactive S679A mutant of Escherichia coli LonA protease ( Ec Lon) has been determined by cryo-EM at the resolution of 3.5 Å. Ec LonA without a bound substrate adopts a hexameric open-spiral quaternary structure that might represent the resting state of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
3
24
0
2
Order By: Relevance
“…Finally, we attempted to find out if the cytosolic domain of the asymmetric FtsH cryo-EM map possesses the staircase arrangement observed in other AAA ATPases (20,27) with the help of the high resolution structure of the YME1 protease (20). Its model (PDB ID: 6AZ0) describes an active state of YME1 during substrate processing, with four subunits bound to ATP, one to ADP, and one free of nucleotides, which gave rise to an asymmetric cytosolic domain (Figures 1, 4 and 5 in (20)).…”
Section: Cryo-emmentioning
confidence: 99%
“…Finally, we attempted to find out if the cytosolic domain of the asymmetric FtsH cryo-EM map possesses the staircase arrangement observed in other AAA ATPases (20,27) with the help of the high resolution structure of the YME1 protease (20). Its model (PDB ID: 6AZ0) describes an active state of YME1 during substrate processing, with four subunits bound to ATP, one to ADP, and one free of nucleotides, which gave rise to an asymmetric cytosolic domain (Figures 1, 4 and 5 in (20)).…”
Section: Cryo-emmentioning
confidence: 99%
“…1 and Supplementary Table 1). The organization is reminiscent of the left-handed, open lockwasher configurations previously observed for substrate-free bacterial Lon 26,28 , although human LONP1 appears to oligomerize with a slightly smaller helical pitch than the bacterial forms (Fig. 1c,d and Supplementary Fig.…”
Section: Substrate-bound and Substrate-free Structures Of Human Lonpmentioning
confidence: 53%
“…The LONP1 protease consists of an N-terminal domain involved in substrate recognition and oligomerization, a AAA+ (ATPases associated with diverse cellular activities) domain that that powers substrate translocation, and a C-terminal serine protease domain involved in substrate proteolysis 1,4,18 . Numerous biophysical approaches have been employed to gain insight into the macromolecular structure and function of bacterial Lon [19][20][21][22][23][24][25][26][27] , and recent cryo-electron microscopy (cryo-EM) studies of bacterial Lon in both substrate-free and substrate-bound conformations revealed the structural basis for substrate processing and protease activation 28 . However, few structural studies have been directed towards understanding the molecular mechanism of protease activation and substrate processing by human LONP1.…”
Section: Introductionmentioning
confidence: 99%
“…For scoring parameters, BLOSUM62 matrix was used with the gap cost: Existence: 11 Extension: 1 with a threshold value of 0.005. In case of both the sequences, the A chain of PDB ID 6U5Z [14] showed the highest query coverage and percentage identity. In case of Uniprot ID P0A9M0 i.e.…”
Section: Sequence Homology Search and Modeling Of The Proteinsmentioning
confidence: 99%